Vocabulary of the Orthodox Church in Cross-cultural Communication: Array - Shyliaeva, Tetyana (Journal of Danubian Studies and Research, 2020)
The article deals with the translation problems in the process of rendering the vocabulary of the Orthodox Church in English cross-cultural communication. Life stories of Saint Anna of Kashin, who is especially revered by the Old Believers or “Lipovans” of the Danube region, were used as the study material. The observation method showed that the most widely used ways of rendering the Orthodox church vocabulary are transcription and transliteration, loan translation and half-calques. Descriptive explaining is often used to clarify the meaning of the unknown realia. The paper contributes to the development of cross-cultural studies. The results can be used in training translators and interpreters.